Effect of mining activities on the rhizosphere soil bacteria of seven plants in the iron ore area - Yan, Xiyue; Huang, Xingting; Liu, Bingliang; Pan, Huimei; Li, Qiang (Frontiers in Microbiology, 2025)
IntroductionMining-induced changes in soil composition, coupled with the persistent challenge of heavy metal pollution, drive structural shifts in soil bacterial communities.MethodsThis study employed ICP-OES and other methods to analyze soil physicochemical properties and performed 16S rRNA sequencing of rhizosphere bacteria to investigate the impact of iron ore mining on the diversity and composition of rhizosphere bacteria in the western Yunnan-Guizhou Plateau.ResultsThe results indicated that the soil nutrient and heavy metal concentrations underwent notable changes due to mining activities. Rhizosphere soil was significantly enriched in Fe and Cu (p < 0.05), but was deficient in alkaline nitrogen (AN) and available phosphorus (AP). Microbial α-diversity was positively correlated with total nitrogen (TN) and organic carbon (OC) but negatively correlated with available potassium (AK) and heavy metal content. Polygonum plebeium R.Br. significantly enriched multidrug-resistant Pseudarthrobacter, while the rhizosphere of Casuarina equisetifolia L. was dominated by the oligotrophic bacterium RB41.DiscussionThis study reveals critical plant-microbe interactions in a mining-disturbed ecosystem and provides a scientific basis for developing microbial indicators and microbe-oriented restoration strategies.